مقاربة الإدغام في اللسان العربي في ضوء الصواتة التوليدية متعددة الأبعاد: The Approach of Assimilation in The Arabic Language by Relying on the Multidimensional Generative Phonology - Abdelaziz Khalil (Universitas Ahmad Dahlan, 2022)
The article deals with the approach of the phenomenon of assimilation of the Arabic language, by relying on multidimensional generative phonology. We will try to interpret the phenomenon and to clarify the phonological changes that occur in it, as well as solve some problems associated with it, based on principles and parameters, especially with regard to the types of syllables and their structure and the interaction that takes place between their components while basing on the data of the Arabic language.